2019
DOI: 10.1101/629378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concurrent Guidance of Attention by Multiple Working Memory Items: Behavioral and Computational Evidence

Abstract: AbstractDuring visual search, task-relevant representations in visual working memory (VWM), known as attentional templates, are assumed to guide attention. A current debate concerns whether only one (Single-Item-Template hypothesis, or SIT) or multiple (Multiple-Item-Template hypothesis, or MIT) items can serve as attentional templates simultaneously. The current study was designed to test these two hypotheses. Participants memorized two colors, prior to a visual-search task in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…While this theoretical framework (Olivers et al, 2011 ) received considerable support over the past years, a growing body of evidence challenges its core assumptions. First, studies using similar paradigms showed that more than one representation was able to interact with visual search at a time (Carlisle & Woodman, 2019 ; van Loon et al, 2017 ; Zhou et al, 2020 ). For instance, it has been demonstrated that memory-based interference increased with two “accessory” representations and two corresponding distractors (Chen & Du, 2017 ; Fan et al, 2019 ; Frătescu et al, 2019 ; Hollingworth & Beck, 2016 ).…”
Section: Wm and Visual Searchmentioning
confidence: 99%
“…While this theoretical framework (Olivers et al, 2011 ) received considerable support over the past years, a growing body of evidence challenges its core assumptions. First, studies using similar paradigms showed that more than one representation was able to interact with visual search at a time (Carlisle & Woodman, 2019 ; van Loon et al, 2017 ; Zhou et al, 2020 ). For instance, it has been demonstrated that memory-based interference increased with two “accessory” representations and two corresponding distractors (Chen & Du, 2017 ; Fan et al, 2019 ; Frătescu et al, 2019 ; Hollingworth & Beck, 2016 ).…”
Section: Wm and Visual Searchmentioning
confidence: 99%